PENGARUH HALAL KNOWLEDGE, ISLAMIC RELIGIOSITY, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA SAKINAH SUPERMARKET DI KOTA SURABAYA - Annisa, Zhella; Nabila, Aliza Salsa; Mardiana, Lena; Fahrullah, Arasy (Universitas Negeri Surabaya, 2024)
The retail business in Indonesia has experienced rapid growth and development in recent years. The retail sector has shown a 15.6% increase compared to the previous year's decline of -14.6%, which can be considered a shift from negative to positive. This is also reflected in the experience of Sakinah Supermarket in Surabaya, which has managed to survive amidst the growing presence of non-sharia modern retail. This study aims to determine whether Halal Knowledge, Islamic Religiosity, and Service Quality influence the purchasing decisions of Surabaya residents to buy from and become consumers at Sakinah Supermarket. A quantitative model method is applied in this research, where numerical data is collected, processed, and analyzed using multiple linear regression to provide an overview of the partial and simultaneous influence between the independent and dependent variables. The results of the study indicate that Halal Knowledge, Islamic Religiosity, and Service Quality have a positive and significant effect on consumer purchasing decisions at Sakinah Supermarket in Surabaya. The implications of these findings suggest that improving halal knowledge, religiosity, and service quality at Sakinah Supermarket can enhance consumer purchasing decisions. Therefore, management should strengthen these three factors to attract more customers who prioritize halal aspects and a quality shopping experience in an increasingly competitive market.